Transforming Employee Engagement and Mental Health Towards Competitive Advantage: Employee Experience as a Catalyst for Change - Nandaru Kelono Bawono (Universitas Kristen Indonesia Toraja, 2024)
Modern organizations face significant challenges in maintaining employee well-being amidst the pressures of ever-increasing transformation. The transformation process often creates a gap between the need to strategically adapt and the organization’s ability to maintain employee mental health and engagement. In this context, it is important for organizations to not only focus on the purpose of the change but also pay attention to its impact on employee work experience. This study aims to explore the relationship between work experience, employee engagement, and mental health as critical elements in a digital transformation strategy to achieve competitive advantage. Through a literature review approach, this study analyzes various studies from reliable sources to identify patterns and relationships between digital transformation and its impact on employees. Using thematic analysis, this study uncovers key concepts such as the role of digitalization in shaping work experience, the dynamics of employee engagement, and the importance of mental health as a foundation for organizational success. The findings of this study provide an in-depth understanding of how transformation can be managed effectively by combining aspects of technology and employee well-being. As a result, organizations are expected to be able to create a productive, innovative, and well-being-supportive work environment, so that they can achieve sustainable competitive advantage.